2001
DOI: 10.1177/014572170102700307
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Certified Diabetes Educator in Telephone Counseling

Abstract: Telephone-based counseling is a brief, effective, ongoing intervention that gives patients with diabetes immediate access to CDEs who provide education to support lifestyle behavioral changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…These content areas are presented in behavioral terms and thereby exemplify the importance of action-oriented, behavioral goals and objectives (13,21,55,121123,128,129). Creative, patient-centered experience-based delivery methods are effective for supporting informed decision-making and behavior change and go beyond the acquisition of knowledge.…”
Section: Standardsmentioning
confidence: 99%
“…These content areas are presented in behavioral terms and thereby exemplify the importance of action-oriented, behavioral goals and objectives (13,21,55,121123,128,129). Creative, patient-centered experience-based delivery methods are effective for supporting informed decision-making and behavior change and go beyond the acquisition of knowledge.…”
Section: Standardsmentioning
confidence: 99%
“…Over a 6-month period, this service significantly improved stages of readiness for physical activity among patients with type 2 diabetes. 43 In addition, it nearly doubled walking activity for adults enrolled in a pedometer-based walking program. 44 Improving the results that physician counseling generates may be the key to increasing its frequency and making it a systemic, sustained part of clinical encounters.…”
Section: Broader Implications and Recommendationsmentioning
confidence: 99%
“…Woo et al (2005) reported that individualized dietary consultation using a diabetic buffet system was effective for helping patient to understand their diet prescriptions and controlling body weight and blood sugar level. Hayes et al (2001) and Maljanian et al (2005) have demonstrated the effectiveness of telephone consultations in diabetes management. Therefore, various approaches of nutrition education including telephone consultation are urgently needed to achieve more effective management of diabetes.…”
Section: Introductionmentioning
confidence: 99%